Independensi Lembaga Swadaya Masyarakat (LSM) di Tengah Kepentingan Donor - Assadi, Husain; Hadi Dharmawan, Arya; Adiwibowo, Soeryo (Sodality: Jurnal Sosiologi Pedesaan, 2009)
The top-down development approach has failed to bring Indonesia in meeting prosperity. Alternatively, a critical approach as offered by Non Governmental Organization (NGO) becomes much more attractive to be adopted. However such approach encounters problematics since each NGO carries its own interest, ideology, and its dependency on donor agencies, normally diametrically collide with another NGO’s ideology, its interest as well as donor-supported interest. This study is to answer the question how deep have donors infleunced to the ideology, interest, and financial independency of local NGOs. The study use qualitative method as approach. The financial arrangement network, action, interest, motives and NGOs’ ideologies are the main focus of this study. Two NGOs are observed, namely Lembaga Kajian untuk Transformasi Sosial (LKTS) and Lembaga Pertanian Sehat (LPS). This study revealed that LKTS and LPS were quite dependent in the financial aspect. LKTS was also dependent in formulating action, while LPS was independent. Some factors affecting the independence of NGOs are: (1) degree of militancy of NGOs’ ideology, (2) financial strength, (3) NGOs’ level of achievements. In the development perspective, NGOs are not necessarily reflecting type of social movement organization which are always strongly based on bottom-up ideology.